Dexmedetomidine sedation for endobronchial ultrasound-guided transbronchial needle aspiration, a randomised controlled trial. Issue 4 (10th November 2020) - Lin, Ting-Yu; Huang, Yu-Chen; Kuo, Chih-Hsi; Chung, Fu-Tsai; Lin, Yu-Ting; Wang, Tsai-Yu; Lin, Shu-Min; Lo, Yu-Lun
Background and aim: Appropriate sedation is important to the success of endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA). Dexmedetomidine is a sedative agent that operates via the α2 adrenergic agonist, which provides sleep-like sedation with little respiratory suppression. This study compared the efficacy and safety of dexmedetomidine sedation with propofol in cases of EBUS-TBNA. Methods: Patients requiring EBUS-TBNA were randomly assigned dexmedetomidine sedation (D, n=25) or propofol sedation (P, n=25). Vital signs, diagnostic yield and the bispectral index (BIS) were recorded throughout the bronchoscopic procedure and recovery period. The tolerance and cooperation of the patients were evaluated using questionnaires. Measurements and results: The lowest mean arterial blood pressure in group D (79.2±9.9 versus 72.5±12.9 mmHg, p=0.049) exceeded that in group P, the lowest heart rate was lower (60.9±10.2 versus 71.4±11.8 beats·min −1, p=0.006) and the mean BIS during sedation was significantly higher (84.1±8.3 versus 73.6±5.7, p<0.001). Patients in group D were more likely to report perceiving procedure-related symptoms and express an unwillingness to undergo the bronchoscopy again, if indicated (41.1 versus 83.3%, p=0.007). One subject in group D aborted EBUS-TBNA due to intolerance. Many of the variables in the two groups were similar, including the proportion of hypoxaemic events, recovery times, patient cooperation and diagnostic yield. Conclusions: The effects of dexmedetomidine on haemodynamics were in line with its pharmacodynamic features. Patients who received dexmedetomidine were more likely than those who received propofol to perceive the procedures. Overall, dexmedetomidine did not prove inferior to propofol sedation in terms of patient cooperation or diagnostic yield. Compared to propofol sedation for EBUS-TBNA, dexmedetomidine provided patients lighter sedation with lower heart rates and less decrease in blood pressure. The recovery times, hypoxaemia, cooperation and diagnostic yield in the two groups were similar. https://bit.ly/33qgEj3